Effect of Reducing Sugar and Total Nitrogen to Ethanol Production from Molasses by Saccharomyces cerevisiae - Ekwan Nofa Wiratno; Tri Ardyati; Agustin Krisna Wardani (Journal of Experimental Life Science)
Indonesia's oil production has declined, while demand for derivative products is increasing. Objective of this research are to understand effect of reducing sugar and total nitrogen variation to ethanol production and fermentation efficiency, cell viability, acidity, temperature, dissolved oxygen with molasses by Saccharomyces cerevisiae (SAF Instant). Step of this research consist of determination of reducing sugar, ethanol fermentation, total nitrogen determination, ethanol determination and data analysis. Treatment of reducing sugar (GR) and total nitrogen (N) (g.L-1) that are GR 100 N 0, GR 100 N 6, GR 100 N 10, GR 125 N 0, GR 125 N 6 and GR 125 N 10. Fermentation was carried out for 72 hours with three replications. Observation parameters every 24 hours are ethanol and reducing sugar concentration, temperature, acidity and dissolved oxygen. Highest ethanol resulted from GR 125 N 6 (3.68 g.L-1) and GR 100 N 6 (3.53 g.L-1). Low reducing sugar consumption inhibited by by-product of yeast metabolism and molasses chemical compound, lead leaves high sugar concentration (> 80 g.L-1). GR 100 N 6 and GR 125 N 6 have highest fermentation efficiency (69 and 57 %). There was no increase in temperature and decrease in pH significantly (α>0.05). Dissolved oxygen decreased significantly (α>0.05) at the early of fermentation and decrease until the end of fermentation. Total nitrogen 6 g g.L-1 has the highest fermentation efficiency.